Detection of Smuggled Genetically Modified Crops and Assessment of its Environmental Impact in the Ethio -Sudan Trans Boundary Area, North West Ethiopia - Nega, Berhane; Mulu, Muche; Zewdu, Teshome (Journal of Biotechnology and Biomedical Science, 2023)
Background The genetic material of the genetically modified crop has been altered to develop the necessary insect resistance features by introducing genes from the Bt (Bacillus thuringiensis) bacterium. The objective of this study was to find smuggled GM Bt crops in the Metema farming area and examine its environmental effects. Method An experimental; Completely Randomized Design (CRD) was used to collect crop samples in the study area. The CTAB (Cetyltrimethyl ammonium bromide) technique was used to isolate DNA from all transported samples, and the purity was determined using a Nano Drop spectrophotometer. Conventional PCR with particular primers for different Bt gene events was used to detect the presence of genes. Furthermore, utilizing Bt cotton specific primer sets, the prevalence of GM cotton was measured, and amplified fragments were confirmed using agarose gel electrophoresis. Result The PCR results revealed that 15 (33.3 percent) of the samples were Bt cotton smuggled from Sudan. The PCR assay also revealed the presence of GM maize. Moreover, the effects of GM genes on the environment were studied in diseased samples, and no transgenes were found. Furthermore, domestic and indigenous crops were used to determine horizontal gene transfers of GM genes to other crops, and the transgene was not found in any of the samples analyzed. Conclusion: In the current study, 28 (13.4%) of the 209 (100%) total analyzed samples were GM crops which indicated the presence of unauthorized GM seeds in the study area. Environmental impact studies and horizontal gene transfer data similarly revealed that the Bt gene was not transferred to other crops and had no harmful environmental effects. For a better understanding of the Impact of imported unauthorized GM seeds, more additional detection of GM events should be done by expanding the sampling site and sample types.
Keywords: Biosafety; Bt-crop; Bt-gene; Environmental impact; Gene flow